Fintech Literacy-Inclusion and Its Impact on Generation Z: Study of Islamic State University Students in Central Java, Indonesia - Ismanto, Kuat; Syamsuddin; Syafiqah, Aina; Jazlina, Nurin (Journal of Islamic Economics Perspectives, 2024)
This research aims to analyse Generation Z's involvement with Fintech loans in terms of literacy and inclusion and their impact on their lives. This study was conducted as field research with a mixed approach (quantitative and qualitative). As a first step, researchers surveyed five Islamic Religious Universities in Central Java using a questionnaire (G-Form) with 177 respondents. From the survey results, researchers deepened the data by conducting in-depth interviews with ten informants who were selected according to predetermined criteria. The data that has been obtained is analysed descriptively and qualitatively using an interactive model. This research shows that Generation Z at these five Islamic-based campuses has quite good literacy with online loans, as demonstrated by understanding the conceptual-operational definitions and risks. There are also funds from online loans used to meet college needs, such as buying a laptop and other college support needs. Because their literacy and inclusion are pretty good, they have good repayment strategies, such as studying while working, opening a business, etc. However, generation Z's involvement with online loans has more or less disrupted their psychology in living and studying.